Pemanfaatan Paket ddp di Software R untuk Analisis Pola Pangan Harapan - Weksi Budiaji; Rifqi Ahmad Riyanto; Suherna Suherna (Amerta Nutrition, 2021)
Background: Desirable dietary pattern (DDP) is a variety of food nutrition intake that is calculated based on energy (calory) consumption. A DDP index close to 100 has a meaning that the food intake varies. Badan Ketahanan Pangan RI (BKP) and Nutrisurvey have developed a DDP index calculation software. As an alternative, ddp package of R software can be also calculated ddp index.Objectives: To apply the ddp package of Software R in calculating and analyzing DDP of individuals both descriptive and inferential analyses and to compare the ddp package with the application of PPH Susenas and Nutrisurvey Software. Methods: This research applied survey and simulation methods. The survey was conducted on the 3rd-semester students of the Food Technology Department, University of Sultan Ageng Tirtayasa via an online survey. They administered both closed questions about dietary patterns and opened questions of a list of their daily food intake. Calculation and analysis of the DDP applied in the valid data in the ddp package of software R. The DDP analyses were followed by both descriptive and inferential analyses including t-test and simple linear regression.Results: The ddp packaged required 7 minutes to input the menu data of each person per day. Compared to Nutrisurvey, it required only 5 minutes. There were different results between the ddp package and Nutrisurvey because a category of food could absent in the Nutrisurvey databases. The harmonization application of the DDP analysis Susenas, on the other hand, had similar results. Both descriptive and inferential analyses as a further analysis can be applied easily. The descriptive analysis showed that the majority of respondents had a low value of energy, protein, and carbohydrate, while the inferential statistic resulted in that the food expenditure more than 70% significantly affected the DDP score.Conclusions: The ddp package could calculate and analyzed the DDP very well and had an equal result with the harmonization application of the DDP analysis susenas. Although the application process of the ddp package required a longer time than that of Nutrisurvey, the databases of the ddp package were more precise and suitable for the DDP calculation and analysis in Indonesia.